Influence of the Mass Rapid Transit System on Plotted Residential Property Prices: A Case Study of Gurugram, India - Fandian, Sneh; Panwar, Manoj (Alanya Üniversitesi, 2025)
Mass Rapid Transit Systems (MRTS) are increasingly recognised as critical drivers of urban transformation, particularly in rapidly urbanising cities at the Global level. However, empirical research on their influence on plotted residential property markets in emerging urban contexts remains limited. This study investigates the socio-economic impact of the Delhi Metro Line extension in Gurugram, India, across the various phases of the metro project. Using a mixed-methods approach, it combines a hedonic price modelling of 300 residential properties from 2007 to 2024 with qualitative surveys and spatial analysis. The study measures